Body mass index and sex and their effect on patient-reported outcomes following cartilage repair: an insight from the International Cartilage Regeneration and Joint Preservation Society Patient Registry - Gwenllian F. Tawy; Reza Ojaghi; Michael J. McNicholas (Elsevier, 2024)
Introduction: Chondral injuries in the knee, whether isolated or accompanying other injuries are found in as many as 60% of arthroscopic examinations. Although current research has identified negative outcomes for patients with a body mass index (BMI) >30kg/m2 undergoing chondral repair, our understanding of the relationship between presurgery BMI and postoperative patient-reported outcomes across all BMI categories remains lacking. Objectives: Through the International Cartilage Regeneration and Joint Preservation Society (ICRS) Patient Registry, this study aimed to explore this relationship, taking into account sex variations. Methods: The ICRS Patient Registry was used to extract the data for this study. The outcomes in focus were the Knee Osteoarthritis Outcome Score (KOOS) and EQ-5D scores. Pearson and Spearman correlation methods were applied and the level of significance was set as α= 0.05. Results: Of 3194 Registry patients at the time of data extraction, 1757 had undergone a surgical procedure, and 336 of these had complete KOOS or EQ-5D scores available for 6-week, 6-month, and 1-year postoperation. Analyses revealed that neither male (average BMI - 28.2 kg/m2) nor female (average BMI - 25.3 kg/m2) data sets indicated a correlation between BMI and the patient-reported outcomes. Conclusions: BMI, irrespective of sex, is not correlated with patient-reported outcomes in patients enrolled in the ICRS Registry with a BMI <30 kg/m2. Although BMIs in the overweight classification were not associated with poorer outcomes than BMIs in the normal classification, the current literature continues to support the notion that a BMI >30 kg/m2 is linked to poor cartilage repair and failure.